The science of footwear - Goonetilleke, Ravindra S. (Human factors and ergonomics, 2013)
"Covering every aspect of the process, this book introduces the design, development, manufacturing, and marketing of footwear. It also presents a comprehensive discussion of how the footwear industry attempts to cater to the wide needs of sophisticated and demanding customers. The text provides a basic understanding of the technology and techniques involved in the design and development of a popular and demanding consumer product. Topics include the measurement and testing process, foot and footwear interaction, mass customization, the manufacturing process, and the marketing process. The author also addresses the latest trends in footwear technology"-- Vydavatelská anotace